SPESIES LALAT BUAH (DIPTERA: TEPHRITIDAE) PADA CABAI YANG DIJUAL DI TIGA PASAR UTAMA KOTA PEKANBARU - Ahmad Taufiq Arminudin; Penti Suryani; Muhammad Dhuhron Yusuf (Jurnal Agroteknologi, 2012)
This study conducted on October to December 2011 in three markets of Pekanbaru Province of Riau; there were Arengka market, Sukaramai market, and Kodim market. The purposes of this study were to know fruit flies species on chili sold in the three market of Pekanbaru and find its distribution channels. Research used questioner-interview to chili and chili pepper’s sales and host rearing method to collect the fruit flies. Host rearing method applicated to incubate rotten chili and chili pepper from the three market of Pekanbaru until the fruit flies imago emerge. Fruit flies were identified using a software intkey for windows ver. 511 and confirmed with the fruit fly expert. The study found two species of fruit flies from red chili (Capsicum annum var. longum L.), chili pepper (C. frustescens), and red curly chili (C. annum), there were Bactrocera papayae (Drew & Hancock) and B. latifrons (Hendel). Bactroceca papayae were most dominating fruit fly species on imported chili and chili peppers at Pekanbaru, whereas B. latifrons were most investing species on chili peppers.